2016
DOI: 10.1073/pnas.1601773113
|View full text |Cite
|
Sign up to set email alerts
|

EBV noncoding RNA EBER2 interacts with host RNA-binding proteins to regulate viral gene expression

Abstract: Epstein-Barr virus (EBV) produces a highly abundant noncoding RNA called EBV-encoded RNA 2 (EBER2) that interacts indirectly with the host transcription factor paired box protein 5 (PAX5) to regulate viral latent membrane protein 1/2 (LMP1/2) gene expression as well as EBV lytic replication. To identify intermediary proteins, we isolated EBER2-PAX5-containing complexes and analyzed the protein components by mass spectrometry. The top candidates include three host proteins splicing factor proline and glutamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…After invasion of host cells, some virus-encoded proteins are used to regulate the host's environment, thus helping to increase virus replication (50)(51)(52)(53).Previous studies have revealed that the nsp1 proteins of coronaviruses can regulate the host protein synthesis and help the virus escape the host's immune interference (25,27,43,45,54). The highly variable sequence homology of the coronavirus nsp1 proteins may lead to the diverse mechanisms for inhibiting the host gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…After invasion of host cells, some virus-encoded proteins are used to regulate the host's environment, thus helping to increase virus replication (50)(51)(52)(53).Previous studies have revealed that the nsp1 proteins of coronaviruses can regulate the host protein synthesis and help the virus escape the host's immune interference (25,27,43,45,54). The highly variable sequence homology of the coronavirus nsp1 proteins may lead to the diverse mechanisms for inhibiting the host gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Two maximum likelihood-based methods, the dynamic histogram analysis method (DHAM) and the general transition-based reweighting analysis method (TRAM), 5962 were proposed recently to provide free energy estimates for multi-state simulations when the simulations at some λ -states are only locally equilibrated. As we propose for Stratified-UWHAM, both DHAM and TRAM require building MSMs first for further analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum likelihood function of TRAM is a product of the maximum likelihood functions of binless WHAM (population counts) and DHAM (transition counts). 62 Unlike Stratified-UWHAM, TRAM stratifies every λ -state into configuration states (macrostates) of MSMs. The local free energy of each configuration state at each λ -state is calculated during each iteration of TRAM analysis: the free energy differences between the same configuration states at different λ -states are calculated in a binless manner; the free energy differences between configuration states at each λ -state are calculated based on the transition counts and the detailed balance condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this region includes the terminal repeats, and the virus – linear in the virion – needs to recircularize before LMP2 can be transcribed, and perhaps before this region is properly regulated. In addition the terminal repeats contain a binding site for PAX5, which is directed to the viral genome by EBER2 [74]. Two of the factors reported to bind to the EBER2/PAX5 complex (NONO and SPFQ) have also been reported to bind to EBNA-LP in a tandem affinity mass spectrometry experiment [75], although these two proteins both have a high background signal in such experiments according to the CRAPome repository [76].…”
Section: Discussionmentioning
confidence: 99%